Analyzing spatial configurations of various supermarkets through space syntax and its relationship with consumers' spatial cognition - Dave, Othello Ricardo IV G. (2019)
This study aimed to explore the role of spatial configuration on the spatial cognition (wayfinding) of an individual in a complex shopping environment specifically, a supermarket. Searching for desired products in these vast spaces holds a significant portion in the shopping experience of a customer which often results in customer dissatisfaction/frustration, especially when spatial configuration is poor within these venues. The reason being is that the venturing of spaces due to unintelligibility of planning causes the product searching activity to take up majority of the customer?s time and effort. The goal of this research was to understand the influence of these various space layouts on the movement/behavior of these consumers and how to manipulate these findings in order to achieve maximum intelligibility and give a responsive stimulus to customers and improve their wayfinding. The findings of the study were that the syntactic value of integration proves to be strongly correlated with a shopper?s number of times spent inside the supermarket and as well as the number of times a shopper seeks assistance from staff/personnel. This implies that the higher integration value, the higher amount of effort that a shopper exerts inside the supermarket.